Social representations elaborated by elderly people about being elderly or aged: structural and procedural approaches - Laércio Deleon de Melo; Cristina Arreguy-Sena; Antônio Marcos Tosoli Gomes; Pedro Miguel Dinis Parreira; Paulo Ferreira Pinto; Júlio Cézar Cruz Collares da Rocha (Universidade Federal de Santa Maria, 2020)
Objective: to discuss the social representations of people aged ≥65 years about being elderly or aged. Method: research outlined in the Theory of Social Representations. Elderly people from Minas Gerais Basic Health Unit participated. Sociodemographic characterization data were collected and evocation technique and recorded interviews were applied in 2015, with prototypical and content analyzes, supported by softwares. Results: 93 elderly people participated, mostly women (62.4%), aged 72 years on average and with ≤8 years of education (88.15%). Nuclear contents were identified - common: "evaluates-being-old" and distinct: "age-arrives" and "experience" (being elderly) and "difficult-bad" (being aged). In the procedural approach, engagement to deal with new demands was identified, despite the recognition of secondary limitations to the aging process. Conclusion: there was an absence of objective nuclear contents, with behaviors and thoughts anchored in one's experiences and in other people's, linked to the level of (in)dependency, living conditions and support networks, carrying similarities and distinctions.